KUALITAS PAPAN PARTIKEL DARI KULIT BATANG SAGU (Metroxylon spp) DENGAN PEREKAT ALAMI ASAM SITRAT: SIFAT FISIK, SIFAT MEKANIK, DAN KEAWETAN TERHADAP RAYAP TANAH Coptotermes curvignathus Holmgren - Dwi Cahyo Nugroho; Gusti Eva Tavita; Dina Setyawati (Tengkawang : Jurnal Ilmu Kehutanan, 2018)
The study aimed to analyze the quality of particle boards from bark fiber of sago (Metroxylon spp) with citric acid as natural adhesives based on physical properties, mechanical properties, and durability from subterranean termites Coptotermes curvignathus Holmgren. Particle boards are made with a size of 30 cm x 30 cm x 1 cm. The experimental factors used in the study included densities (0.7 gr/cm3 and 0.8 gr/cm3) and concentrations of citric acid adhesives (20% and 30%). The material then flow into hotpress with 1800C for 15 minutes and pressure at 25 kg/cm2. Testing of the physical and mechanical properties of particle boards refers to the JIS A 5908-2003 standard and durability against subterranean termites Coptotermes curvignathus Holmgren was conducted based on SNI 01. 7207-2006. The results showed that the densities factor had a significant effect on density, thickness swelling, MOE, MOR, internal bond, screw holding strength, and weight loss of the particle board against termites. Meanwhile concentration of citric acid adhesive significantly affected the density, moisture content, water absorption, thickness swelling, MOR, internal bond, and screw holding strength. The interaction between the densities factor and concentration of citric acid has a significant effect on thickness swelling and density. The physical and mechanical properties of particle boards which fulfill the JIS A 5908 2003 standard were density, moisture content, MOR, and screw holding strength. The durability of particleboard againts termites has a very strong level. The average values of termites mortality were 94% ~ 100%. The average of wood weight loss values were 9.61%~ 18.51%. The particle board made with a density 0.8 gr/cm3 and concentration of citric acid adhesive 30% achieved the highest values on physical properties, mechanical properties and durability to the termites Coptotermes curvignathus. Keywords : citric acid, Coptotermes curvignathus, Metroxylon spp, particle board, sago